2017
DOI: 10.1139/cjpp-2017-0280
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the response to angiotensin II between left and right ventricular endocardial endothelial cells

Abstract: Previous studies focused on the right ventricular endocardial endothelial cells (EECRs) and showed that angiotensin II (Ang II) induced increase in cytosolic and nuclear calcium via AT receptor activation. In the present study, we verified whether the response of left EECs (EECLs) to Ang II is different than that of EECRs. Our results showed that the EC of the Ang II-induced increase of cytosolic and nuclear calcium in EECLs was 10× higher (around 2 × 10 mol/L) than in EECRs (around 8 × 10 mol/L). The densitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…Atef and Anand-Srivastava, including other authors, have demonstrated that the Gqα protein-related signaling pathway is a classical pathway of the hypertrophic response of VSMCs [ 33 , 34 ]. Generally, this pathway can be triggered by growth factors, or by one or more varieties of vasoactive substances, including angiotensin II, endothelin-1and neuropeptide Y [ 19 , 21 , 32 , 35 ].…”
Section: Vascular Remodelingmentioning
confidence: 99%
“…Atef and Anand-Srivastava, including other authors, have demonstrated that the Gqα protein-related signaling pathway is a classical pathway of the hypertrophic response of VSMCs [ 33 , 34 ]. Generally, this pathway can be triggered by growth factors, or by one or more varieties of vasoactive substances, including angiotensin II, endothelin-1and neuropeptide Y [ 19 , 21 , 32 , 35 ].…”
Section: Vascular Remodelingmentioning
confidence: 99%
“…The same group proposed that the balance of AT 1 /AT 2 receptor ratio is critical in the antagonistic actions between the two receptors (Miura et al 2010). Hence, the difference in the receptor type involved in Ang II-induced apoptosis between EECRs and EECLs in our study could be due to the difference in the ratio of AT 1 /AT 2 receptors at the plasma membrane level in these two cell types (Jacques et al 2017b).…”
Section: Discussionmentioning
confidence: 61%
“…Among these differences, our group has shown that the distribution of Ang II and its receptors, AT 1 and AT 2 , is different between EECRs and EECLs (Jacques et al 2003a(Jacques et al , 2017b. Also, EECLs are more sensitive to Ang II stimulation than EECRs (Jacques et al 2017b).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations